1983
DOI: 10.1007/bf03350556
|View full text |Cite
|
Sign up to set email alerts
|

Antiandrogenic properties of spironolactone. Clinical trial in the management of female hirsutism

Abstract: The effect of spironolactone on female hirsutism was studied in 18 patients. The drug was administered at the dose of 400 mg for the first ten days and 300-200 mg later on in a first group of women (Group A); a second group (Group B) was given 200 mg spironolactone for the whole length of therapy. A significant decrease of the index of Ferriman and Gallwey (p = 0.01) was noted from the 100th day of treatment; acne and seborrhoea improved concomitantly. Plasma total testosterone values fell from 0.64 +/- 0.24 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The location of lesions was reported in only three case series [48, 54, 57]. Seven studies did not make a clear statement about concomitant medications, making attribution of any clinical effect to spironolactone uncertain [41, 43–45, 49, 51, 55]. Further details are reported in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The location of lesions was reported in only three case series [48, 54, 57]. Seven studies did not make a clear statement about concomitant medications, making attribution of any clinical effect to spironolactone uncertain [41, 43–45, 49, 51, 55]. Further details are reported in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…f The behavior of gonadotropins after SP seems to differ among sexes. Whereas, in men FSH and LH were observed to rise (149), an irregular and anovulatory pattern was seen in hirsute females (188). As mentioned before, "Blffignandi et al (139) have reported an increase in free estradiol coupled with a decrease in free T after in vitro mcubation of plasma from healthy males with SP.…”
Section: Management Of Hirsutism With Spmentioning
confidence: 85%
“…After this initial report, a number of papers appeared (169,188,(190)(191)(192)(193)(194). The role of this drug for this particular indication is well established now.…”
Section: Management Of Hirsutism With Spmentioning
confidence: 93%
See 1 more Smart Citation
“…After this initial report a number of papers from both our group and other researchers appeared, and now the role of SP for this particular indication is well established [8].…”
Section: Cyproterone Acetatementioning
confidence: 95%